Exact receptance function and receptance curvature of a clamped-clamped continuous cracked beam - Khoa, Nguyen Viet; Mai, Cao Van; Thao, Dao Thi Bich (Vietnam Journal of Mechanics, 2019)
The receptance function has been studied and applied widely since it interrelates the harmonic excitation and the response of a structure in the frequency domain. This paper presents the derivation of the exact receptance function of continuous cracked beams and its application for crack detection. The receptance curvature is defined as the second derivative of the receptance. The influence of the crack on the receptance and receptance curvature is investigated. It is concluded that when there are cracks the receptance curvature has sharp changes at the crack positions. This can be applied for the crack detection purpose. In this paper, the numerical simulations are provided.